CFTR: a hub for kinases and crosstalk of cAMP and Ca2+. (27th August 2013) - Kunzelmann, Karl; Mehta, Anil
Abstract : Cystic fibrosis (CF) is caused by mutations in the CF transmembrane conductance regulator (CFTR). The resulting disease is pleiotropic consistent with the idea that CFTR acts as a node within a network of signalling proteins. CFTR is not only a regulator of multiple transport proteins and controlled by numerous kinases but also participates in many signalling pathways that are disrupted after expression of its commonest mutant (F508del‐CFTR). It operates in membrane compartments creating a scaffold for cytoskeletal elements, surface receptors, kinases and phosphodiesterases. CFTR is exposed to membrane‐local second messengers such that a CFTR‐interacting, low cellular energy sensor kinase (AMP‐ and ADP‐activated kinase, AMPK) signals through a high energy phosphohistidine protein kinase (nucleoside diphosphate kinase, NDPK). CFTR also translocates a Ca 2+ ‐dependent adenylate cyclase to its proximity so that a rigid separation between cAMP‐dependent and Ca 2+ ‐dependent regulation of Cl − transport becomes obsolete. In the presence of wild‐type CFTR, parallel activation of CFTR and outwardly rectifying anoctamin 6 Cl − channels is observed, while the Ca 2+ ‐activated anoctamin 1 Cl − channel is inhibited. In contrast, in CF cells, CFTR is missing/mislocalized and the outwardly rectifying chloride channel is attenuated while Ca 2+ ‐dependent Cl − secretion (anoctamin 1) appears upregulated. Additionally, we consider the idea that F508del‐CFTR when trapped in the endoplasmic reticulum augments IP3 ‐mediated Ca 2+ release by providing a shunt pathway for Cl − . CFTR and the IP3 receptor share the characteristic that they both assemble their partner proteins to increase the plasticity of their hub responses. In CF, the CFTR hub fails to form at the plasma membrane, with widespread detrimental consequences for cell signalling. Abstract : The Cystic Fibrosis protein CFTR is not just a chloride channel but acts as a membrane scaffold for many other proteins linked to cell calcium and cyclic AMP. Here, we merge these themes by examining the ins and outs of signal pathways that either control CFTR or are controlled by CFTR. We focus on kinase‐kinase (Figure), channel‐kinase and channel‐channel interactions.